SCREENING OF THE RECOMBINANT INBRED LINE MAPPING POPULATION OF RICE DERIVED FROM CROSS WAZUHOPHEK X IMPROVED SAMBA MAHSURI FOR LOW SOIL P TOLERANCE - M.S.ANATHA; R. M. SUNDARAM, R.R. KALE, M. ANILA, H. K.MAHADEVA SWAMY , V. P. BHADANA, CH. V. DURGA RANI (The Journal of Research, PJTSAU, 2019)
Rice (Oryza sativa L.) is one of the principal staple food crops, which feeds a major portion of the world’s population. Various biotic and abiotic stresses viz., plant diseases, pests, water scarcity, salinity, soil nutrient deficiencies and a rapidly changing climate affects the rice production significantly. In the present study, an effort was made to develop breeding lines in the genetic background of the elite, bacterial blight (BB) resistant, fine-grain type rice variety, Improved Samba Mahsuri (ISM) for tolerance to soil phosphorus (P) deficiency by using the rice line, Wazuhophek (possessing non-Pup1 type low soil P tolerance), as the donor. Hybridization was made between Wazuhophek and Improved Samba Mahsuri and the derived recombinant inbred line (RIL) mapping population (n = 330; F8 generation) was screened for low soil P tolerance in the low soil P plot (available P < 2 kg ha-1) of ICAR-IIRR, Hyderabad, India and also in the normal soil P plot for their resistance against bacterial blight. A total of 191 RILs were tolerant to low soil P condition. Two RILs (KR-100 and KR-295) were identified with higher yield under low P conditions with desirable medium slender grain type. These breeding lines have the potential in saving significant production costs in application of phosphatic fertilizers and increasing profits of farmers.